2020
DOI: 10.3390/pr8080989
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Induces the Formation of Biofilm of Bacteria from Different Phases of Wastewater Treatment

Abstract: The study monitored the effect of tetracycline on bacterial biofilm formation and compared biofilm formation by resistant bacterial strains in different phases of the wastewater treatment process in wastewater treatment plant (WWTP). The crystal violet staining method was used to evaluate the biofilm formation. Biofilm-related bacterial properties were characterized by hydrophobicity, autoaggregation and motility tests. The relative abundance of tetracycline resistance genes (tetW, tetM, tetO, tetA and tetB) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
3
2
0
Order By: Relevance
“…In strains of Escherichia coli and Pseudomonas aeruginosa, sub-inhibitory concentrations of tetracycline and cephradine induce biofilm formation and increase the transfer rate of the pB10 plasmid among the biofilm biomass at higher rates compared with no antimicrobial treatment [54]. The findings from the current study were congruent with a previous report [55] that resistant bacteria could form biofilms. Tetracycline-resistant Bacillus sp.…”
Section: Discussionsupporting
confidence: 90%
“…In strains of Escherichia coli and Pseudomonas aeruginosa, sub-inhibitory concentrations of tetracycline and cephradine induce biofilm formation and increase the transfer rate of the pB10 plasmid among the biofilm biomass at higher rates compared with no antimicrobial treatment [54]. The findings from the current study were congruent with a previous report [55] that resistant bacteria could form biofilms. Tetracycline-resistant Bacillus sp.…”
Section: Discussionsupporting
confidence: 90%
“…MIC values for tetracycline were mostly in the range of 0.25-8.0 µg/mL, while for 33% of isolates from S_A and 10% of isolates from D_B, MIC values of >16 µg/mL were confirmed (Figure 5). These values agree with certain studies [51,52]. However, compared to other studies, our MIC values are somewhat lower.…”
Section: Samplingsupporting
confidence: 92%
“…MIC values for tetracycline were mostly in the r 0.25-8.0 μg/mL, while for 33% of isolates from S_A and 10% of isolates from D_ values of >16 μg/mL were confirmed (Figure 5). These values agree with certain [51,52]. However, compared to other studies, our MIC values are somewhat low example, Svobodová et al ( 2018) discovered the presence of eight bacterial strai Czech wastewater showing MICs for tetracycline >100 mg/mL [27].…”
Section: Samplingsupporting
confidence: 83%
“…The copyright holder for this preprint this version posted February 5, 2024. ; https://doi.org/10.1101/2024.02.03.24302270 doi: medRxiv preprint aph( 6)-ld, and aph('3')-lb, could be linked to prolonged clinical use of sulfonamides and aminoglycosides both within and outside clinical settings. Multiple studies have also reported the most abundant ARG gene identified, tet(G), from hospital wastewater together with other tetracycline genes, attributing this difference to the overuse or misuse of antibiotics [31,32]. These core antibiotics could be used to monitor the spread of ARGs across different sites before they are released into the environment.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%